(untitled) (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This article aims to analyze the concept of educational supervision from the perspective of the Qur’an and Hadith as a normative basis for the implementation of Islamic educational supervision. This study uses a qualitative approach with a library research type. Data were obtained from primary sources in the form of verses of the Qur’an and Hadith relevant to the concept of supervision, guidance, and evaluation in education, and supported by various scientific literature related to Islamic educational supervision. Data were analyzed using content analysis techniques through the stages of identification, classification, interpretation, and synthesis of supervision themes found in the study sources. The results of the study indicate that the concept of supervision in Islam is built on three main principles, namely (1) muraqabatullah (awareness of Allah’s supervision) as the basis for the integrity and responsibility of the supervisor, (2) the principle of shura (deliberation) and nasihah (advice) as a mechanism for guidance and feedback, and (3) the principle of amar ma’ruf nahi munkar as an orientation for continuous improvement and development. These findings demonstrate that educational supervision, from an Islamic perspective, functions not only as an administrative oversight activity but also as a development process oriented toward strengthening morals, professionalism, and spiritual responsibility. This study contributes to the development of a humanistic, transformative, and prophetic value-based model of Islamic educational supervision.